The Contribution of FMRP to the Development of Speech and Vocabulary in Young Boys with Fragile X Syndrome: A Retrospective Examination - Stephen R. Hooper; John Sideris; Deborah R. Hatton; Joanne R. Roberts (Children)
Background/Objectives: This study examined the development of speech, expressive vocabulary, and receptive vocabulary in boys with Fragile X Syndrome (FXS), with a focus on the contribution of the Fragile X Messenger Ribonucleoprotein (FMRP), while controlling for the effects of nonverbal IQ, maternal education, and Autism status on the development of these skills. Methods: Participants included 45 boys with full mutation FXS, ranging in age from 2.9 to 14.0 years, who were subdivided into those with FXS only (FXS-Only) and those with FXS and Autism (FXS-Autism). Speech, expressive vocabulary, and receptive vocabulary skills were assessed over three years for each participant. Results: There was a significant relationship between each of the outcome measures and the child’s nonverbal mental level, and between for both outcome measures of vocabulary and Autism status, but these relationships were moderated by the level of FMRP. Specifically, higher levels of FMRP seemed to increase the relationship between developmental level of speech, receptive, and expressive vocabulary for boys with FXS with and without Autism; however, at lower levels of FMRP, these relationships seemed to weaken significantly for both groups. Conclusions: These findings implicate increased complexity in the relationship between various contributors to the rates of growth of speech, expressive vocabulary, and receptive vocabulary in boys with FXS, with FMRP being a key variable potentially moderating the relationship between nonverbal abilities, Autism status, and speech and vocabulary development.